Large Language Models in Healthcare: Applications and Critical Limitations - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2025)
Explore how large language models enhance healthcare through documentation, diagnosis, and education, with critical insights on their limitations and clinical use.
Keywords: Large Language Models; AI in Healthcare; Clinical Documentation; Differential Diagnosis; Patient Education